MIDWIFERY CARE IN THE POSTPARTUM PERIOD FOR MRS. E IN KAJHU VILLAGE, SUB-DISTRICT BAITUSSALAM, THE DISTRICT OF ACEH BESAR IN 2026: MIDWIFERY CARE IN THE POSTPARTUM PERIOD - Mulia Azzahra zahra; Salmiani Abdul Manaf; Satrinawati Berkat (Journal of Midwifery and Community Health (JMCH), 2026)
Maternal Mortality (MMR) remains a major health problem globally and in Indonesia. Complications during the postpartum period, such as bleeding, infection, and eclampsia, significantly contribute to the increase in MMR. Comprehensive and continuous midwifery care during the postpartum period is necessary to detect complications early and support maternal recovery. This case report aims to provide postpartum midwifery care to Mrs. E and document it in a SOAP format. Care was provided to Mrs. E, 34 years old, G3P2A0, 6 hours postpartum, with a history of normal, spontaneous delivery and second-degree perineal laceration in Kajhu Village, sub-district Baitussalam, thedistrict of Aceh Besar. Subjective data indicated that the mother still experienced abdominal cramps, body aches, and cramps after delivery, and her breast milk flowed smoothly. Objective examination results indicated that the mother was in good general condition, with blood pressure of 100/70 mmHg, fundal height of two finger-widths below the umbilicus, palpable uterine contractions, and normal lochia rubra. The care provided included education on cramps and mobilization techniques, postpartum exercises, perineal wound care, breastfeeding counseling, and education on postpartum danger signs. The results showed that the mother understood all the counseling provided. Comprehensive midwifery care during the first postpartum visit is expected to support the mother's recovery and prevent complications.